2016
DOI: 10.1038/srep36591
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetic retinopathy using new mydriasis-free, full-field flicker ERG recording device

Abstract: Diabetic retinopathy (DR) is a leading cause of blindness among working-age adults. Therefore, it is important to detect DR accurately during mass screening. The purpose of this study was to determine whether a small, hand-held, mydriasis-free, full-field flicker electroretinographic (ERGs) device called RETeval can be used to screen for DR. To accomplish this, we recorded full-field flicker ERGs with this device from 48 normal eyes and 118 eyes with different severities of DR in patients with diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 31 publications
2
46
2
Order By: Relevance
“…Therefore, we believe that the differences of 1.5 ms associated with pupil size or axial length are substantial when considering the classification of patients for flicker ERGs. 23 There are three limitations in this study. The first limitation is that we measured mainly the fundamental component of flicker ERGs while the measurements of the peak implicit times or peak-to-peak amplitudes are more generally used in clinical situations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, we believe that the differences of 1.5 ms associated with pupil size or axial length are substantial when considering the classification of patients for flicker ERGs. 23 There are three limitations in this study. The first limitation is that we measured mainly the fundamental component of flicker ERGs while the measurements of the peak implicit times or peak-to-peak amplitudes are more generally used in clinical situations.…”
Section: Discussionmentioning
confidence: 91%
“…The components of the RETeval system have been described in detail. [16][17][18][19][20][21][22][23] In brief, full-field stimuli are presented with a 60-mm diameter dome, and the white stimuli are created by a combination of three colored light emitting diodes. The frequency of the flicker stimulus was 28.306 Hz, and the pulse duration was less than 1 msec.…”
Section: Flicker Erg Recordings By Retevalmentioning
confidence: 99%
See 1 more Smart Citation
“…In later stages of the disease, the photopic single-flash b-wave and flicker ERG can become reduced in amplitude and/or delayed. 20 – 23 Given these findings, as well as the recent availability of a portable instrument for recording the flicker ERG, there has been renewed interest in the flicker ERG as a tool to screen for sight-threatening DR. 24 26 Previous studies of the flicker ERG in diabetes have almost exclusively elicited the response by using full-field periodic flashes of light at a flicker rate of approximately 30 Hz, the frequency recommended by international standards. 27 However, a recent report from our group has shown value in recording the ERG elicited by higher flicker rates.…”
mentioning
confidence: 99%
“…There are several reports of the presence of supernormal ERG amplitudes in eyes with retinal vascular disorders including eyes with diabetic retinopathy 17,18 and CRVO. [19][20][21][22] In 1992, Gouras and Mackay 21 reported that 4 of 12 eyes with a CRVO had supernormal single-flash cone ERGs when conventional white flash stimuli were used.…”
Section: Discussionmentioning
confidence: 99%